Backyard Farming: An Environmental Income of an Indigenous People in the Philippines - Jainar, Hannah Dominique; Arsenal, Roland Raphael; Esmaña, Gabriela; Galaura, Airich Jane; Herminanda, Khent John; Ana, Laiza Mae Sta.; Pedroso, John Erwin (Far Western Review, 2025)
Indigenous people can sustain themselves through various activities, including backyard farming as a source of environmental income. This qualitative descriptive research aimed to analyze the capability of an Aeta community to perform backyard farming as an environmental income source. The study utilized semi-structured interviews to gather information from seven (7) informants. Informants were selected using a purposeful sampling technique. The gathered information was analyzed using the Braun & Clarke thematic analysis approach. Results revealed that Aetas are able to adapt toward different backyard farming challenges through practical strategies such as sack gardening, water-saving methods, and the use of traditional knowledge, demonstrating creativity and resilience despite limited resources. These findings highlight the importance of indigenous knowledge and adaptive practices in promoting sustainable backyard farming for environmental income.